Enhancing Environmental Awareness and School Entrepreneurship through Smart Farming and Solar Energy Based Waste Processing - Andi Rizal; Achmad Fajar Muhammad; Sri Agustini; Ahmad Swandi; Sri Rahmadhanningsih; Andio Calen Evains (Universitas AMIKOM Yogyakarta, 2026)
The Community Partnership Program (PKM), entitled Increasing Environmental Awareness and School Entrepreneurship through Smart Farming and Solar-Based Waste Processing, aimed to enhance environmental awareness and strengthen school entrepreneurship in Pangkajene Kepulauan Regency, Indonesia. The program engaged teachers and students through three integrated innovations: (1) a solar-powered aquaponics smart farming system, (2) an educational waste-processing unit (eco-station), and (3) a mini solar power plant (PLTS). These innovations created a contextual and sustainable learning ecosystem while addressing limited knowledge of waste management, renewable energy, and entrepreneurship. The program resulted in a moderate improvement in teachers’ understanding (N-Gain >= 0.5), the establishment of a school waste-processing unit, and the implementation of contextual science lesson plans by more than 70% of teachers. In addition, the school produces 5–6 kg of vegetables and catfish weekly, approximately 105 kg of compost within six months, and at least two value-added products. More than 30 students actively participated in production and distribution activities, fostering entrepreneurial and environmental competencies. Overall, the program strengthened school capacity and contributed to SDGs 4 (Quality Education), 7 (Affordable and Clean Energy), 12 (Responsible Consumption and Production), and 13 (Climate Action)